Elongating under Stress - de Nadal, Eulàlia (SAGE-Hindawi Access to Research, 2011)
In response to extracellular stimuli, mitogen-activated protein kinases (MAPKs) modulate gene expression to maximize cell survival. Exposure of yeast to high osmolarity results in activation of the p38-related MAPK Hog1, which plays a key role in reprogramming the gene expression pattern required for cell survival upon osmostress. Hog1 not only regulates initiation but also modulates other steps of the transcription process. Recent work indicates that other yeast signalling MAPKs such as Mpk1 modulate transcriptional elongation in response to cell wall stress. Similarly, mammalian MAPKs have also been found associated to coding regions of stress-responsive genes. In this paper, significant progress in MAPK-regulated events that occur during the transcriptional elongation step is summarized, and future directions are discussed. We expect that the principles learned from these studies will provide a new understanding of the regulation of gene expression by signalling kinases.